peu-MIR2916-p3-enriched garlic exosomes ameliorate murine colitis by reshaping gut microbiota, especially by boosting the anti-colitic Bacteroides thetaiotaomicron - Xiaoyuan Wang; Yueyue Liu; Xinyue Dong; Tianchi Duan; Chennan Wang; Lu Wang; Xingbin Yang; Honglei Tian; Ting Li (Elsevier, 2024)
Plant-derived exosome-like nanoparticles (ELNs) have drawn considerable attention for oral treatment of colonic diseases. However, the roles of ELNs derived from garlic on colitis remain unclear. Here, we demonstrate that garlic ELNs (GELNs), with desirable particle sizes (79.60 nm) and trafficking large amounts of functional proteins and microRNAs, stably roam in the gut and confer protection against ulcerative colitis (UC). In mice with DSS-induced colitis, orally administered GELNs effectively ameliorated bloody diarrhea, normalized the production of proinflammatory cytokines, and prevented colonic barrier impairment. Mechanistically, GELNs were taken up by gut microbes and reshaped DSS-induced gut microbiota dysbiosis, in which Bacteroides was the dominant respondent genus upon GELNs treatment. Notably, GELNs-enriched peu-MIR2916-p3 specifically promoted the growth of Bacteroides thetaiotaomicron, an intestinal symbiotic bacterium with palliative effects on colitis. Our findings provide new insights into the medicinal application of GELNs and highlight their potential as natural nanotherapeutic agents for preventing and treating UC.